Micro-Mechanism of Silicon-Based Waveguide Surface Smoothing in Hydrogen Annealing - 段倩倩 任馨宇 菅傲群 张辉 冀健龙 张强 张文栋 桑胜波 (Chinese physics letters, 2016)
The micro-mechanism of the silicon-based waveguide surface smoothing is investigated systematically to explore the effects of silicon-hydrogen bonds on high-temperature hydrogen annealing waveguides. The effect of silicon- hydrogen bonds on the surface migration movement of silicon atoms and the waveguide surface topography are revealed. The micro-migration from an upper state to a lower state of silicon atoms is driven by silicon- hydrogen bonding, which is the key to ameliorate the rough surface morphology of the silicon-based waveguide. The process of hydrogen annealing is experimentally validated based on the simulated parameters. The surface roughness declines from 1.523nm to 0.461 nm.